A Comparison of Recalled Pain Memory Following Living Kidney Donation Between Directed and non-Directed, Altruistic Donors. (December 2022) - Katvan, Eyal; Cohen, Jonathan; Rahamimov, Ruth; Ashkenazi, Tamar
Introduction: Pain following donor nephrectomy for living kidney donation is common. In Israel, non-directed, altruistic donations account for 45% of all kidney transplants.Design: This cross-sectional, retrospective survey included 2 groups of donors derived from the data of Israel Transplant, namely directed and non-directed, altruistic donors, who donated between 2015 to 2018. The degree of recalled pain memory post-surgery was assessed using the Visual Analog Scale at 5 time points: immediately post-surgery, after 1 week, 1 month and 3 months post-surgery and in the month preceding completion of the questionnaire. In addition, continued requirement for analgesics for more than one-month post-surgery, the degree of interference with daily activities in the month preceding the questionnaire and the recalled time to return to full-time employment were also noted.Results: In total, 246 (131 directed and 115 non-directed, altruistic) donors were included in the study. Non-directed, altruistic donors reported statistically significantly lower degrees of recalled pain memory at all time points, a lower requirement for prolonged analgesic use and less recalled interference with daily activities due to pain. In addition, these donors recalled returning significantly earlier to full-time employment. Finally, no significant differences in the degree of recalled pain memory were noted for directed donors according to their relation to the recipient, apart from donation to a spouse.Conclusion: These unique findings, if validated in a prospective study, could provide important information to potential non-directed, altruistic donors regarding the expected level of post-surgical pain and their return to full-time employment.